2010
DOI: 10.1212/wnl.0b013e3181ea1564
|View full text |Cite
|
Sign up to set email alerts
|

Redefining dysferlinopathy phenotypes based on clinical findings and muscle imaging studies

Abstract: Splitting dysferlin myopathy into separate phenotypes does not reveal significant differences in terms of rate of progression, prognosis, genotype, or MRI pattern. The finding that proximal and distal muscles are already impaired in the MRI at onset in both MM and LGMD2B favors grouping all phenotypes under the term dysferlin myopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
94
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 34 publications
18
94
5
1
Order By: Relevance
“…The rate of progression of this disease is highly variable among patients, with no correlation between the age of onset of symptoms and the rate at which the muscles deteriorate (32,33). The SJL mouse has previously been described as having a slowly progressive muscular dystrophy by 6 months of age followed by rapid disease progression in subsequent months (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of progression of this disease is highly variable among patients, with no correlation between the age of onset of symptoms and the rate at which the muscles deteriorate (32,33). The SJL mouse has previously been described as having a slowly progressive muscular dystrophy by 6 months of age followed by rapid disease progression in subsequent months (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…4) head), adductor magnus and longus, gastrocnemius medialis and tibialis posterior appeared to be less severely affected. Notably, tibialis posterior is affected early in the disease course, contrary to the majority of myopathies, in particular LDMG and distal myopathies, in which tibialis posterior is frequently spared even in the late-end stages of the disease course [17,[25][26][27][28][29]. Muscles of anterior compartment of the leg are variably affected during the disease course while quadriceps and psoas become affected in the late-end stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Muscles of anterior compartment of the leg are variably affected during the disease course while quadriceps and psoas become affected in the late-end stages of disease. Psoas sparing can help to recognize NLSD from other myopathies in the late-end course of the disease when specificity of the MRI pattern involvement disappears or the muscle biopsy may be not informative [17,[25][26][27][28][29]. Sparing of sartorius, gracilis and pectineus is constantly observed in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have reported the use of muscle MRI as a useful noninvasive technique for the assessment of neuromuscular disorders (Mercuri et al 2002a; De Jager et al 1998;Paradas et al 2010;Fisher et al 2005;Wattjes et al 2010). In this study, the authors introduce a completely new, simple to perform, and reliable diagnostic method to assess the progress of the muscle atrophy process in myopathies.…”
Section: Discussionmentioning
confidence: 99%